Roles of the Crisis Management Initiative (CMI) in Aceh’s Reconciliation to Strengthen Indonesia’s National Integration After Tsunami in 2005 - Mujiburrahman Mujiburrahman (Journal of Maritime Studies and National Integration, 2018)
Crisis Management Initiative (CMI) is a National Government Organization that focuses on advocacy for sustainable security and conflict resolution. This organization was founded in 2000 by Martti Ahtisaari. Ge was the former president of Finland in 1994-2000. CMI was asked to facilitate negotiation between the Indonesian government and GAM (Free Aceh Movement), through personal contact between Farid Husain and Juha Christensen. Aceh conflict was a disintegration-oriented-conflict, so it was potential to threaten Indonesia’s sovereignty.This research used the historical method with heuristic, criticism or verification, interpretation, and historiography stages. The primary sources of data on this research were information in the media, both printed and electronic. Besides, this research also examined or reviewed the literary references that were related and relevant to the research topic. The study was to reveal how the background of CMI's involvement in Aceh peace in 2005, and how the strategic roles of CMI in resolving conflicts until the realization of Aceh peace in 2005 for Aceh remained a part of the Republic of Indonesia (NKRI).The role of CMI as a reputable international institution and getting the trust of both parties, was capable of providing intervention to the conflicting parties so that its role became very strategic in mediating the conflict. The success of CMI was seen from the negotiation held in Helsinki Finland, resulting in the execution of the Memorandum of Understanding (MoU) on August 15, 2005, as a peace agreement. After the signing of the Helsinki MoU, armed conflict stopped, and the social lives were back to normal, and the development process could resume usually.